Computer integrated electronics manufacturing and testing - Arabian, Jack (Manufacturing engineering and materials processing, 1989)
Describes this process at it relates to the electronics industry, focusing on such areas as printed wiring boards, networking, automatic assembly, surface mount technology, tape automated bonding, bar coding, and electro-static discharge. Also studies the effects of group work ethics as a factor in.